Perceived Cultural Relevance as a Cognitive-Affective Mechanism in TAM: Acceptance of PhET Simulations in Mathematics Learning - Anggara, Benny; Sugiman Sugiman; Elly Arliani (International Journal of Interactive Mobile Technologies (iJIM), 2026)
The dynamic ethno-situation (DES) approach integrates ethnomathematics exploration with PhET Simulations to provide an interactive and culturally meaningful mathematics learning experience. This study aims to analyze students’ acceptance of DES using the technology acceptance model (TAM) framework, which is expanded with perceived cultural relevance (PCR). A total of 278 junior high school students from four provinces in Indonesia participated through surveys and thematic interviews. Structural equation modeling (SEM) analysis showed that PCR serves as a link between perceived ease of use (PEOU) and perceived usefulness (PU) of technology, strengthening the effect of PU on students’ intention to use it. These results confirm that the acceptance of learning technology depends not only on ease of use and usefulness but also on the cultural relevance perceived by students. When simulations reflect their cultural context, learning becomes more meaningful, emotionally engaging, and deeply motivating. This study structurally expands TAM by incorporating PCR as a cognitiveaffective mechanism, offering a cross-nationally transferable conceptual framework for designing culturally responsive mobile, AI, and interactive simulation-based digital learning.